Testing Social Preferences for an Economic "Bad": An Artefactual Field Experiment*. (18th January 2013) - Keisner, Deborah Kerley; Messer, Kent D.; Schulze, William D.; Zarghamee, Homa
Abstract We test for social preferences over a commodity in an artefactual field experiment using the random price voting mechanism. Subjects are university staff members, and the commodity is water "contaminated" by a sterilized cockroach. Our results suggest that social preferences exist with respect to commodities and "bads", supporting a more general utility framework for social preferences. Our empirical test allows for the coexistence of three social‐preference models; our results support the models of Fehr and Schmidt (1999) and Charness and Rabin (2002), but not the model of Bolton and Ockenfels (2000). Also, we find that incorporating social preferences improves the efficiency of majority‐rules voting.